Sustainable Entrepreneurship in Rural E-Commerce: Identifying Entrepreneurs in Practitioners by Using Deep Neural Networks Approach - Xie, Guojie; Huang, Lijuan; Bin, Hou; Apostolidis, Chrysostomos; Jiang, Yaohui; Li, Guokai; Cai, Weiwei (Frontiers in Environmental Science, 2022)
The digital divide between urban and rural communities has substantially narrowed as information and communication technology has evolved, enabling increasingly more interactions between urban and rural areas. Rural areas now have the foundation and conditions to take advantage of e-commerce opportunities, which is no longer exclusively a city-centric economic mode. Taking advantage of the Internet's vast resources, many villagers jumped at the opportunity to launch rural e-commerce businesses. Rural inhabitants, however, face several challenges when it comes to starting their own e-commerce enterprises. Meanwhile, local governments and rural e-commerce platform providers, find it difficult to provide accurate help to practitioners and entrepreneurs. To this end, a system of indicators based on a model of entrepreneurial events was developed to identify e-commerce entrepreneurs. And the main objective of this paper is to explore the factors influencing the abilities and expectations of rural residents to set up their own e-commerce businesses in order to provide them with tailored support. Survey data from 162 rural e-commerce practitioners were analyzed using a deep neural network in R. The results reveal that the index system developed in this paper has a good level of reliability and validity, and the prediction approach has a high degree of precision (over 90%), indicating that it can successfully identify rural e-commerce entrepreneurs. Based on the findings of this study, we recommend that local governments and e-commerce businesses work together to address the practical issues of perceived feasibility and desirability for rural e-commerce practitioners. Residents in rural areas who want to start their own businesses can take advantage of the development opportunities provided by the information and communication technology, while local governments should keep up with the speed of digitization and informatization to better manage rural economic growth.